Induction of antioxidant enzyme activity and lipid peroxidation level in ion-beam-bombarded rice seeds - Nuananong Semsang (2018)
Low-energy ion beam bombardment has been used to mutate a wide variety of plant species. To explore the indirect effects of low-energy ion beam on biological damage due to the free radical production in plant cells, the increase in antioxidant enzyme activities and lipid peroxidation level was investigated in ion-bombarded rice seeds. Local rice seeds were bombarded with nitrogen or argon ion beams at energies of 29-60 keV and ion fluences of 1 × 1016ions cm-2. The activities of the antioxidant enzymes; superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), dehydroascorbate reductase (DHAR), glutathione reductase (GR), glutathione S-transferase (GST) and lipid peroxidation level were assayed in the germinated rice seeds after ion bombardment. The results showed most of the enzyme activities and lipid peroxidation levels in both the argon and nitrogen bombarded samples were higher than those in the natural control. N-ion bombardment could induce higher levels of antioxidant enzyme activities in the rice samples than the Ar-ion bombardment. Additional effects due to the vacuum condition were found to affect activities of some antioxidant enzymes and lipid peroxidation level. This study demonstrates that ion beam bombardment and vacuum condition could induce the antioxidant enzyme activity and lipid peroxidation level which might be due to free radical production in the bombarded rice seeds. © 2013 Elsevier B.V. All rights reserved.